Resin composition and thermally conductive sheet

By adding a layered material to the resin composition, the resin composition used in heat dissipation applications for in-vehicle parts maintains thermal conductivity and flexibility even at high temperatures, addressing the challenges of filler aggregation and hardness increase.

JP2025058803APending Publication Date: 2025-04-09DEXERIALS CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023196986
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-28
Filing Date
2023-11-20
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Resin compositions used in heat dissipation applications for in-vehicle parts face challenges in maintaining thermal conductivity and flexibility when exposed to high temperatures for extended periods, due to the aggregation of thermally conductive fillers which increases hardness and reduces flexibility.

Method used

Incorporating a layered material into the resin composition, which includes a binder resin, a thermally conductive filler, and a layered material, helps to disrupt the agglomeration structure of the thermally conductive fillers, thereby maintaining flexibility and thermal conductivity even at high temperatures.

Benefits of technology

The use of a layered material in the resin composition effectively suppresses the decrease in flexibility and maintains thermal conductivity over time, even under high-temperature conditions, ensuring the reliability of heat dissipation applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058803000001_ABST
    Figure 2025058803000001_ABST
Patent Text Reader

Abstract

To provide a resin composition that prevents a decline in flexibility even when a cured product of the resin composition is exposed to high-temperature conditions for a prolonged period.SOLUTION: A resin composition comprises a binder resin 2, a thermally conductive filler 3, and a layered material 4. The layered material 4 is, for example, at least one selected from the group consisting of flaky graphite, flaky boron nitride, and melamine cyanurate. A thermally conductive sheet 1 is a cured product of the resin composition containing the binder resin 2, the thermally conductive filler 3, and the layered material 4.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present technology relates to a resin composition and a thermally conductive sheet. [Background technology]

[0002] In recent years, automobiles have become increasingly electronic, and in-vehicle parts such as EV batteries and ECUs (electronic control units) generate a lot of heat and are used for long periods of time. This means that resin compositions used for heat dissipation applications in in-vehicle parts are required to have high thermal conductivity and heat resistance.

[0003] In general, in order to improve the thermal conductivity of a resin composition, it is necessary to fill the thermally conductive filler at a high density (high filling). In this way, when the amount of the thermally conductive filler in the resin composition is increased, the thermal conductivity of the resin composition is improved, but the amount of the binder resin in the resin composition is relatively decreased, so that the initial hardness of the resin composition after curing tends to be high. In addition, if the resin composition after curing is placed in a high temperature environment for a long time, the hardness of the resin composition after curing increases, the initial flexibility is lost, and the thermal conductivity function of the resin composition may be reduced.

[0004] Methods for solving such problems include, for example, improving durability by adding an antioxidant with a specific structure or by adjusting the hardness of the binder resin by acting on the curing reaction of the binder resin (e.g., Patent Documents 1 and 2).

[0005] Incidentally, one possible mechanism for the decrease in flexibility of a thermally conductive sheet when it is placed under high temperatures for a long period of time is that the thermally conductive filler in the cured resin composition aggregates in a high-temperature environment, restricting the movement of particles and increasing the hardness of the cured resin composition. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2016-30774 A [Patent Document 2] Special Publication No. 2014-534292 Summary of the Invention [Problem to be solved by the invention]

[0007] The present technology has been proposed in view of such conventional circumstances, and provides a resin composition that can suppress a decrease in flexibility even when a cured product of the resin composition is placed under high temperatures for a long period of time. [Means for solving the problem]

[0008] As a result of extensive research, the inventors of the present application have found that adding a layered material to a resin composition reduces the loss of flexibility of the cured resin composition even when used for long periods at high temperatures, thereby making it possible to maintain thermal conductivity for a long period of time.

[0009] The resin composition according to the present technology contains a binder resin, a thermally conductive filler, and a layered material.

[0010] The thermally conductive sheet according to the present technology is a cured product of a resin composition that includes a binder resin, a thermally conductive filler, and a layered substance. Effect of the Invention

[0011] This technology can suppress a decrease in flexibility even when the cured resin composition is placed under high temperatures for a long period of time. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a diagram illustrating an example of the mechanism by which a layered substance suppresses a decrease in flexibility when a thermally conductive sheet is subjected to high temperatures for a long period of time. FIG. 1(A) is a diagram showing an example of the state of a thermally conductive filler in a thermally conductive sheet before the sheet is subjected to high temperatures for a long period of time. FIG. 1(B) is an enlarged view of FIG. 1(A). FIG. 1(C) is a diagram showing an example of a state in which the aggregate structure of the thermally conductive filler particles is easily broken down. [Diagram 2] FIG. 2 is a cross-sectional view showing an example of a semiconductor device to which a thermally conductive sheet is applied. [Diagram 3] FIG. 3 is a graph showing the Asker C hardness versus time after aging of the thermally conductive sheets using the resin compositions of Examples 1 to 7 and Comparative Example 1. [Figure 4] FIG. 4 is a graph showing the Asker C hardness versus time after aging of the thermally conductive sheets using the resin compositions of Example 8 and Comparative Example 2. [Diagram 5] FIG. 5 is a graph showing the Asker C hardness versus time after aging for the thermally conductive sheets using the resin compositions of Example 9 and Comparative Example 3. [Figure 6] FIG. 6 is a graph showing the Asker C hardness versus time after aging for the thermally conductive sheets using the resin compositions of Examples 10 to 14 and Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In this specification, the average particle diameter (D50) of the thermally conductive filler (hereinafter simply referred to as "average particle diameter") refers to the particle diameter at which the cumulative value of the cumulative curve of particle diameter values ​​from the small particle diameter side of the particle diameter distribution is 50% when the entire particle diameter distribution of the thermally conductive filler is 100%. In addition, in this specification, the average particle diameter of the layered material is synonymous with the average particle diameter of the thermally conductive filler. Note that the particle size distribution (particle size distribution) in this specification is determined on a volume basis. For example, a method of measuring the particle size distribution can be performed using a laser diffraction type particle size distribution measuring instrument (device name: mastersizer3000, manufactured by Malvern Panalytical).

[0014] <Resin composition> The resin composition according to the present technology includes a binder resin (hereinafter also referred to as "component a"), a thermally conductive filler (hereinafter also referred to as "component b"), and a layered material (hereinafter also referred to as "component c"). Furthermore, the resin composition according to the present technology may further include other components in addition to the components a, b, and c, as described below, within a range that does not impair the effects of the present technology.

[0015] <Component a> The resin composition according to the present technology contains a binder resin as component a. Component a can be selected according to the properties required for the resin composition, which is a thermally conductive material, such as mechanical strength, heat resistance, and electrical properties. Component a can be selected from the group consisting of thermoplastic resins, thermoplastic elastomers, and thermosetting resins.

[0016] Examples of thermoplastic resins include polyethylene, polypropylene, ethylene-α-olefin copolymers such as ethylene-propylene copolymers, polymethylpentene, polyvinyl chloride, polyvinylidene chloride, polyvinyl acetate, ethylene-vinyl acetate copolymers, polyvinyl alcohol, polyvinyl acetal, fluorine-based polymers such as polyvinylidene fluoride and polytetrafluoroethylene, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polystyrene, polyacrylonitrile, styrene-acrylonitrile copolymers, acrylonitrile-butadiene-styrene copolymer (ABS) resins, polyphenylene-ether copolymers (PPE) resins, modified PPE resins, aliphatic polyamides, aromatic polyamides, polyimides, polyamideimides, polymethacrylic acid, polymethacrylic acid esters such as polymethacrylic acid methyl ester, polyacrylic acids, polycarbonates, polyphenylene sulfide, polysulfones, polyethersulfones, polyethernitriles, polyetherketones, polyketones, liquid crystal polymers, and ionomers.

[0017] Examples of the thermoplastic elastomer include a styrene-butadiene block copolymer or a hydrogenated product thereof, a styrene-isoprene block copolymer or a hydrogenated product thereof, a styrene-based thermoplastic elastomer, an olefin-based thermoplastic elastomer, a vinyl chloride-based thermoplastic elastomer, a polyester-based thermoplastic elastomer, a polyurethane-based thermoplastic elastomer, and a polyamide-based thermoplastic elastomer.

[0018] Examples of the thermosetting resin include crosslinked rubber, epoxy resin, phenol resin, polyimide resin, unsaturated polyester resin, diallyl phthalate resin, addition reaction type silicone resin, condensation reaction type silicone resin, etc. Specific examples of the crosslinked rubber include natural rubber, acrylic rubber, butadiene rubber, isoprene rubber, styrene-butadiene copolymer rubber, nitrile rubber, hydrogenated nitrile rubber, chloroprene rubber, ethylene-propylene copolymer rubber, chlorinated polyethylene rubber, chlorosulfonated polyethylene rubber, butyl rubber, halogenated butyl rubber, fluororubber, urethane rubber, and silicone rubber.

[0019] As the component a, for example, a silicone resin is preferable in consideration of the adhesion between the heat generating surface of the electronic component and the heat sink surface. As the silicone resin, for example, a two-liquid addition reaction type silicone resin can be used, which is composed of a silicone having an alkenyl group as the main component, a base agent containing a curing catalyst, and a curing agent having a hydrosilyl group (Si-H group). As the silicone having an alkenyl group, for example, a polyorganosiloxane having a vinyl group can be used. The curing catalyst is a catalyst for promoting the addition reaction between the alkenyl group in the silicone having an alkenyl group and the hydrosilyl group in the curing agent having a hydrosilyl group. As the curing catalyst, a catalyst well known as a catalyst used in a hydrosilylation reaction can be mentioned, for example, a platinum group-based curing catalyst, for example, a platinum group metal such as platinum, rhodium, palladium, etc., or platinum chloride can be used. As the curing agent having a hydrosilyl group, for example, a polyorganosiloxane having a hydrosilyl group can be used.

[0020] As the addition reaction type silicone resin, a desired commercially available product can be used in consideration of the hardness of the cured resin composition. For example, CY52-272, EG-3100 (all manufactured by Toray Dow Corning Co., Ltd.), KE-1800T, KE-1031, KE-1051J (all manufactured by Shin-Etsu Chemical Co., Ltd.) can be mentioned. Component a may be used alone or in combination of two or more kinds.

[0021] <Component b> The resin composition according to the present technology contains a thermally conductive filler as component b. Component b is dispersed in component a. Component b can be selected from known substances in consideration of the desired thermal conductivity, and examples of the component b include metal hydroxides such as aluminum hydroxide and magnesium hydroxide, metals such as aluminum, copper, and silver, metal oxides such as aluminum oxide and magnesium oxide, metal nitrides such as aluminum nitride, boron nitride, and silicon nitride, carbon nanotubes, metal silicon, and fiber fillers (glass fibers, carbon fibers). Component b may be used alone or in combination of two or more.

[0022] From the viewpoint of improving the thermal conductivity of the resin composition, the resin composition preferably contains a spherical thermally conductive filler as component b. The term "spherical" includes shapes such as almost spherical and elliptical in addition to a perfect sphere, and may have a sphericity of 0.8 or more, for example. The average particle size of spherical magnesium oxide, which is an example of a spherical thermally conductive filler, may be, for example, in the range of 0.1 to 150 μm, or may be in the range of 10 to 150 μm. The average particle size of spherical alumina, which is an example of a spherical thermally conductive filler, may be, for example, in the range of 0.1 to 50 μm, or may be in the range of 5 to 30 μm, or may be in the range of 15 to 25 μm.

[0023] In addition, from the viewpoint of reducing the production cost of the resin composition, it is preferable that the resin composition contains an amorphous thermally conductive filler as component b in addition to the spherical thermally conductive filler. The term "irregular" refers to a shape that is not spherical and has an irregular shape and size, and includes shapes such as crushed, flaky, needle-like, and polyhedral. In addition, it is preferable that the term "irregular" does not include a layered shape such as component c described later. In terms of thermal conductivity and further reducing the production cost of the resin composition, the amorphous thermally conductive filler is preferably a crushed thermally conductive filler, for example, crushed aluminum nitride or crushed aluminum hydroxide. The average particle size of the amorphous thermally conductive filler may be in the range of 0.1 to 100 μm, may be in the range of 0.1 to 10 μm, may be in the range of 1 to 7 μm, or may be in the range of 2 to 5 μm.

[0024] The resin composition may contain, as component b, at least one selected from the group consisting of aluminum nitride, metal hydroxide, metal oxide, and carbon fiber. Examples of the metal hydroxide and metal oxide include aluminum hydroxide, alumina, aluminum nitride, and magnesium oxide. For example, alumina, aluminum nitride, or carbon fiber may be used alone as component b. Examples of the use of component b include a combination of spherical magnesium oxide, spherical alumina, and crushed aluminum nitride, a combination of spherical magnesium oxide, spherical alumina, and crushed aluminum hydroxide, and a combination of spherical magnesium oxide, spherical alumina, and crushed aluminum oxide.

[0025] Component b may be surface-treated, for example by treating component b with a coupling agent such as component d (alkoxysilane compound) described below.

[0026] The content of component b in the resin composition can be appropriately determined according to the desired thermal conductivity. If the content of component b in the resin composition is less than 85% by weight, it tends to be difficult to obtain sufficient thermal conductivity. If the content of component b in the resin composition is more than 95% by weight, it tends to be difficult to fill component b. The content of component b in the resin composition can be 85% by weight or more, or 95% by weight or less.

[0027] Furthermore, when the content of component a in the resin composition is 100 parts by weight, the content of component b in the resin composition can be in the range of 1000 to 1500 parts by weight, or may be in the range of 1000 to 1400 parts by weight.

[0028] When two or more kinds of component b are used in combination, it is preferable that the total amount thereof falls within the above content range.

[0029] <Ingredient c> The resin composition according to the present technology contains a layered material as component c. A layered material is a substance or compound consisting of a single atom having a structure in which a plurality of units having a planar structure are stacked. As described above, by adding component c to a resin composition containing components a and b, it is possible to suppress a decrease in flexibility when a cured product of the resin composition (a thermally conductive sheet described later) is placed under high temperature for a long period of time. Here, a long period of time is, for example, 500 to 1000 hours. Moreover, the high temperature is, for example, 150 to 200°C. The conditions under high temperature for a long period of time are not limited to these numerical ranges.

[0030] FIG. 1 is a diagram for explaining an example of a mechanism by which the layered substance suppresses the decrease in flexibility when the thermally conductive sheet is placed under high temperature for a long period of time. FIG. 1(A) is a diagram showing an example of the state of the thermally conductive filler 3 in the thermally conductive sheet 1 before the thermally conductive sheet 1 is placed under high temperature for a long period of time. FIG. 1(B) is an enlarged view of FIG. 1(A), and FIG. 1(C) is a diagram showing an example of a state in which the aggregated structure of the thermally conductive filler 3 is easily broken. The mechanism by which the layered substance 4 suppresses the decrease in flexibility of the thermally conductive sheet 1 is not clear, but is presumed to be as follows. In the thermally conductive sheet 1 containing a large amount of the thermally conductive filler 3, aggregation of the thermally conductive filler 3 may occur at high temperatures even in the presence of a dispersant (for example, component d described later). At this time, the presence of the layered material 4 between the thermally conductive fillers 3 (between particles) is thought to cause the layers of the multilayer structure of the layered material 4 to shift due to external force, as shown in Figures 1(A) to (C), making the aggregate structure of the thermally conductive fillers 3 with the layered material 4 as missing parts more likely to collapse, thereby reducing the hardness of the thermally conductive sheet 1.

[0031] Component c may be a monatomic substance or compound having thermal conductivity like component b described above, or may be a monatomic substance or compound having no thermal conductivity. Specific examples of component c include monatomic substances or inorganic compounds such as clay minerals, such as flake graphite, flake boron nitride, mica, and talc, and compounds having a melamine skeleton or a cyanuric ring, such as melamine cyanurate.

[0032] An example of component c, flake graphite, is a stack of planar structures called graphene, which have a honeycomb shape and are made of bonds of carbon atoms.

[0033] An example of component c, scaly boron nitride, is a laminate of planar honeycomb structures formed by bonding nitrogen and boron.

[0034] Mica, an example of component c, has a structure different from that of graphene, in which layers of silicon, aluminum, and oxygen sandwich layers of aluminum, magnesium, and oxygen from above and below to form a unit layer, and these unit layers are bonded together with layers of cations. Other compounds with this structure include clay minerals such as bentonite and talc.

[0035] Melamine cyanurate, an example of component c, is an organic compound having a structure in which a melamine skeleton and cyanuric acid are hydrogen-bonded. Since it exhibits a mica-like crystal structure and has a planar structure, it can be considered as a layered substance.

[0036] From the viewpoint of heat resistance of the resin composition and the heat conductive sheet which is a cured product of the resin composition, component c is preferably an inorganic substance or inorganic compound consisting of a single atom, or an organic compound having a rigid planar structure such as a cyanuric ring. For example, a preferred inorganic substance consisting of a single atom which is component c is flake graphite, and for example, a preferred inorganic compound is flake boron nitride.

[0037] In particular, in consideration of suppressing a decrease in flexibility when a thermally conductive sheet, which is a cured product of the resin composition, is placed under high temperatures for a long period of time, component c is preferably at least one selected from the group consisting of flake graphite, flake boron nitride, and melamine cyanurate, and may be at least one of flake graphite and melamine cyanurate, or may be flake graphite or melamine cyanurate, or may be flake graphite.

[0038] Furthermore, from the viewpoint of suppressing a decrease in flexibility when a thermally conductive sheet, which is a cured product of the resin composition, is placed under high temperatures for a long period of time, and also from the viewpoint of reactivity with other materials contained in the resin composition, inorganic substances or inorganic compounds consisting of single atoms, such as flake graphite and flake boron nitride, are preferred.

[0039] Component c may or may not be in contact with component b in the resin composition, but from the viewpoint of more effectively achieving the effects of the present technology, it is preferable that component c is in contact with component b in the resin composition. In addition, the average particle diameter of component c is preferably smaller than the average particle diameter of component b. When the resin composition contains multiple components b with different average particle diameters, component c may contain at least one component b with an average particle diameter smaller than that of the multiple components b. This makes it easier to increase the number of components c in contact with component b, and it is considered that the effects of the present technology can be more effectively achieved. The average particle diameter of component c is not particularly limited, but from the viewpoint of suppressing a decrease in flexibility when a thermal conductive sheet, which is a cured product of the resin composition, is placed under high temperature for a long period of time, it can be in the range of 1 to 30 μm, may be in the range of 2 to 22 μm, may be in the range of 2 to 15 μm, may be in the range of 2 to 10 μm, may be in the range of 2 to 5 μm, or may be 22 μm or less.

[0040] The content of component c in the resin composition is preferably not too high from the viewpoint of suppressing a decrease in flexibility when a thermally conductive sheet, which is a cured product of the resin composition, is placed under high temperatures for a long period of time. For example, the content is preferably 30% by weight or less, may be 20% by weight or less, may be 10% by weight or less, may be 5% by weight or less, may be 4.5% by weight or less, may be 4.2% by weight or less, may be 4.1% by weight or less, may be 4.0% by weight or less, may be 3.5% by weight or less, may be 3.2% by weight or less. It may be 3.0% by weight or less, may be 2.5% by weight or less, may be 2.1% by weight or less, may be 0.50% by weight or less, may be 0.33% by weight or less, may be 0.30% by weight or less, may be 0.25% by weight or less, may be 0.20% by weight or less, may be 0.18% by weight or less, may be 0.17% by weight or less, may be 0.16% by weight or less, may be 0.10% by weight or less, or may be 0.07% by weight or less.

[0041] Furthermore, the lower limit of the content of component c in the resin composition is not particularly limited, but from the viewpoint of more effectively suppressing a decrease in flexibility when a thermally conductive sheet, which is a cured product of the resin composition, is placed under high temperatures for a long period of time, the lower limit is preferably, for example, 0.07% by weight or more, and may be 0.08% by weight or more.

[0042] From the viewpoints of suppressing a decrease in flexibility when a thermally conductive sheet, which is a cured product of the resin composition, is placed under high temperatures for a long period of time and minimizing the effect of component c on thermal conductivity and thermal resistance, the content of component c in the resin composition is preferably in the range of 0.07 to 4.5% by weight, may be in the range of 0.07 to 4.0% by weight, may be in the range of 0.07 to 2.0% by weight, may be in the range of 0.07 to 0.33% by weight, or may be in the range of 0.07 to 0.17% by weight.

[0043] Furthermore, from the viewpoint of suppressing a decrease in flexibility when a thermally conductive sheet, which is a cured product of the resin composition, is placed under high temperatures for a long period of time, the content of component c relative to the total content of components b and c in the resin composition (component c / (component b+component c)) may be in the range of 0.09 to 4.72% by weight.

[0044] When two or more kinds of component c are used in combination, it is preferable that the total amount of component c in the resin composition satisfies the above-mentioned range of the content of component c.

[0045] <ingredient d> As described above, the resin composition according to the present technology may further contain an alkoxysilane compound as component d, in addition to components a, b, and c, as necessary.

[0046] For example, when the resin composition contains a large amount of component b, it is preferable to further contain component d from the viewpoint of further improving the dispersibility of component b. As a guideline for using component d, for example, when the content of component a in the resin composition is 100 parts by weight, it is preferable to use component d when the content of component b is 1200 parts by weight or more. Not limited to this example, component d may be used when the content of component b is 1500 parts by weight or more, or when the content of component b is less than 1200 parts by weight, when the content of component a in the resin composition is 100 parts by weight.

[0047] Component d is a so-called silane coupling agent having an alkyl group or a reactive group. Component d is a compound having a structure in which one to three of the four bonds of a silicon atom are bonded to an alkoxy group, and the remaining bonds are bonded to an organic substituent.

[0048] Examples of the alkoxy group of component d include a methoxy group, an ethoxy group, a protoxy group, a pentoxy group, and a hexatoxy group. From the viewpoint of availability, component d is preferably a compound having a methoxy group or an ethoxy group. From the viewpoint of further increasing the affinity with component b, the number of alkoxy groups of component d is preferably 2 or more, and more preferably 3. A specific example of component d is preferably at least one selected from a trimethoxysilane compound and a triethoxysilane compound.

[0049] Examples of functional groups contained in the organic substituent of component d include an acryloyl group, an alkyl group, a carboxyl group, a vinyl group, a methacryl group, an aromatic group, an amino group, an isocyanate group, an epoxy group, a hydroxyl group, and a mercapto group. From the viewpoint of further increasing the dispersibility of component b in the resin composition and facilitating higher loading of component b, component d is preferably an alkylalkoxysilane compound having an alkyl group bonded to a silicon atom, that is, an alkyl group-containing alkoxysilane compound. In the alkyl group-containing alkoxysilane compound, the number of carbon atoms of the alkyl group bonded to the silicon atom is preferably 4 or more, may be 6 or more, may be 8 or more, or may be 10 or more. In addition, from the viewpoint of further reducing the viscosity of the resin composition, in this alkyl group-containing alkoxysilane compound, the number of carbon atoms of the alkyl group bonded to the silicon atom is preferably 16 or less, may be 14 or less, or may be 12 or less. In addition, in the alkyl group-containing alkoxysilane compound, the alkyl group bonded to the silicon atom may be linear, branched, or cyclic.

[0050] Examples of alkyl group-containing alkoxysilane compounds, which are examples of component d, include methyltrimethoxysilane, dimethyldimethoxysilane, trimethylmethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, ethyltrimethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, isobutyltrimethoxysilane, isobutyltriethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, cyclohexylmethyldimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, and hexadecyltrimethoxysilane. Among the alkyl group-containing alkoxysilane compounds, at least one selected from isobutyltrimethoxysilane, isobutyltriethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, cyclohexylmethyldimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, and hexadecyltrimethoxysilane is preferred, and at least one of n-decyltrimethoxysilane and hexadecyltrimethoxysilane is more preferred.

[0051] When the resin composition contains component d, the content of component d in the resin composition is not particularly limited, but for example, when the content of component b in the resin composition is 100 parts by weight, it can be 0.1 parts by weight or more, can be in the range of 0.1 to 2.0 parts by weight, or can be in the range of 0.2 to 1.0 parts by weight. The content of component d in the resin composition can also be in the range of 0.1 to 1.5% by weight with respect to the total amount of component b. When two or more kinds of component d are used in combination, it is preferable that the total amount satisfies the above content range.

[0052] <ingredient e> The resin composition according to the present technology may further contain an antioxidant as component e, if necessary, in addition to components a, b, and c. For example, the resin composition may further contain component e from the viewpoint of more effectively maintaining the thermal conductivity function.

[0053] As component e, for example, a hindered phenol-based antioxidant can be used. The hindered phenol-based antioxidant, for example, captures radicals and contributes more effectively to suppressing the oxidative deterioration of component a.

[0054] Examples of the hindered phenol-based antioxidant include those having a structure represented by the following formula 1 as a hindered phenol skeleton. The hindered phenol-based antioxidant preferably has one or more skeletons represented by the following formula 1, and may have two or more skeletons represented by the following formula 1.

[0055] (Formula 1) [ka]

[0056] In formula 1, R 3 and R 4 represents a t-butyl group, and R 5 When represents a hydrogen atom (hindered type), R 3 represents a methyl group, and R 4 represents a t-butyl group, and R 5 When represents a hydrogen atom (semi-hindered type), R 3 represents a hydrogen atom, and R 4 represents a t-butyl group, and R 5 It is preferable that represents a methyl group (less hindered type).

[0057] The hindered phenol-based antioxidant may have an ester bond in its structure. Examples of such component e include stearyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, pentaerythritol tetrakis[3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate], and 2,2'-dimethyl-2,2'-(2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diyl)dipropane-1,1'-diyl=bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propanoate]. In addition, the hindered phenol-based antioxidant may also be one that does not have an ester bond in its structure, such as 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane.

[0058] Commercially available products of component e include, for example, Adeka STAB AO-30, Adeka STAB AO-50, Adeka STAB AO-60, Adeka STAB AO-80 (all manufactured by ADEKA Corporation), Irganox 1010, Irganox 1035, Irganox 1076, Irganox 1135 (all manufactured by BASF Corporation).

[0059] When the resin composition contains component e, the lower limit of the content of component e in the resin composition can be, for example, 0.1 parts by weight or more, and can also be 0.5 parts by weight or more, when the content of component a in the resin composition is 100 parts by weight. The upper limit of component e in the resin composition can be, for example, 10 parts by weight or less, and can also be 5 parts by weight or less, when the content of component a in the resin composition is 100 parts by weight. When two or more types of component e are used in combination, it is preferable that the total amount thereof satisfies the above content range.

[0060] The thermal conductive sheet 1 may further contain other components in addition to the above-mentioned components, as long as the effect of the present technology is not impaired. Examples of the other components include dispersants, curing accelerators, retarders, tackifiers, plasticizers, flame retardants, stabilizers, metal deactivators, and colorants.

[0061] The resin composition according to the present technology can be obtained, for example, by kneading the above-mentioned components using a mixer (for example, a planetary kneader, a ball mill, a Henschel mixer, or the like).

[0062] <Thermal Conduction Sheet> The thermally conductive sheet according to the present technology is a cured product of a resin composition containing the above-mentioned components a to c.

[0063] From the viewpoint of achieving high thermal conductivity, the thermal conductive sheet according to the present technology preferably has a higher thermal conductivity, and for example, the thermal conductivity in the thickness direction (initial thermal conductivity) can be 3 W / (m·K) or more, 4 W / (m·K) or more, 5 W / (m·K) or more, or 6 W / (m·K) or more, or can be in the range of 3.83 to 6.93 W / (m·K). The thermal conductivity of the thermal conductive sheet can be measured by the method described in the examples below.

[0064] Furthermore, the thermal conductive sheet according to the present technology has good heat resistance reliability in terms of thermal conductivity, and can suppress a decrease in thermal conductivity even when placed under high temperatures for a long period of time. The thermal conductive sheet according to the present technology can have a thermal conductivity in the thickness direction of 3 W / (m·K) or more, 4 W / (m·K) or more, 5 W / (m·K) or more, or 6 W / (m·K) or more, or can be in the range of 3.51 to 5.82 W / (m·K), for example, after being placed in an environment of 170°C for 500 hours. The thermal conductivity of the thermal conductive sheet can be measured by the method described in the examples below.

[0065] The thermal conductive sheet according to the present technology can have an initial Asker C hardness, in other words, an Asker C hardness after the thermal conductive sheet is produced and before the thermal conductive sheet is placed under high temperature for a long period of time of 43 or less, or 35 or less, or 33 or less, or 32 or less, or 30 or less, or 29 or less, or 27 or less, or 26 or less, or 25 or less, or 21 or less, or in the range of 20 to 60, or in the range of 21 to 43. Thus, the thermal conductive sheet according to the present technology has good initial flexibility. The Asker C hardness of the thermal conductive sheet can be measured by the method described in the examples below.

[0066] In addition, the thermally conductive sheet according to the present technology has good heat resistance reliability in terms of hardness, and can suppress a decrease in flexibility even when placed under high temperatures for a long period of time. The thermally conductive sheet according to the present technology can have an Asker C hardness of 70 or less, 59 or less, 56 or less, 49 or less, or in the range of 30 to 59, after being placed in an environment of 170°C for 500 hours. Thus, since the thermally conductive sheet according to the present technology has good heat resistance reliability, it can be suitably used, for example, for heat dissipation applications of in-vehicle parts that are used for a long period of time with a high amount of heat generation.

[0067] Furthermore, the thermal conductive sheet according to the present technology can have an Asker C hardness of 60 or less, or can be 59 or less, or can be 58 or less, or can be 57 or less, or can be 56 or less, or can be 49 or less, or can be 47 or less, or can be 37 or less, or can be in the range of 20 to 60, after being placed in an environment of 170°C for 250 hours.

[0068] The thermal conductive sheet according to the present technology may have a breakdown voltage of, for example, 0.1 kV / mm or more, 2 kV / mm or more, 5 kV / mm or more, 7 kV / mm or more, 8 kV / mm or more, or 9 kV / mm or more, or may be in the range of 0.1 to 9 kV / mm. The breakdown voltage of the thermal conductive sheet may be measured by the method described in the examples below.

[0069] From the viewpoint of preventing short circuits in electronic circuits around semiconductor elements, for example, the thermal conductive sheet according to the present technology has a volume resistivity of 1.0×10 at an applied voltage of 1000 V. 10 (Ω cm) or more is preferable, and 1.0×10 14 The upper limit of the volume resistivity of the thermal conductive sheet is not particularly limited and can be appropriately selected depending on the purpose. For example, the upper limit is 1.0×10 18 The volume resistivity of the thermal conductive sheet can be measured by the method described in the examples described below.

[0070] The thermally conductive sheet according to the present technology can be obtained by applying the above-mentioned resin composition to a desired thickness on a release film formed from, for example, PET (polyethylene terephthalate), PEN (polyethylene naphthalate), polyolefin, polymethylpentene, glassine paper, etc., and leaving it at room temperature for 24 hours or more to harden the component a. The thickness of the thermally conductive sheet can be appropriately selected depending on the purpose, and can be, for example, in the range of 0.05 to 5 mm.

[0071] <Electronic equipment> The thermally conductive sheet according to the present technology can be arranged between a heat generating body and a heat sink to form an electronic device (thermal device) in which the heat generated by the heat generating body is dissipated to the heat sink. The thermally conductive sheet according to the present technology can suppress the loss of flexibility even when placed under high temperatures for a long period of time as described above, and therefore can further reduce the risk of malfunctions in electronic devices.

[0072] The electronic device has at least a heat generating body, a heat sink, and a thermally conductive sheet, and may further have other members as necessary. The heat generating body is not particularly limited, and examples thereof include electronic components that generate heat in an electric circuit, such as integrated circuit elements such as a CPU, a GPU (Graphics Processing Unit), a DRAM (Dynamic Random Access Memory), and a flash memory, transistors, resistors, etc. The heat generating body also includes components that receive optical signals, such as an optical transceiver in a communication device. The heat generating body also includes the power devices described above as applications of the resin composition.

[0073] The heat dissipator is not particularly limited, and examples thereof include heat sinks and heat spreaders that are used in combination with integrated circuit elements, transistors, optical transceiver housings, etc. Examples of materials for heat sinks and heat spreaders include copper and aluminum. In addition to heat spreaders and heat sinks, the heat dissipator may be anything that conducts heat generated from a heat source and dissipates it to the outside, and examples of the heat dissipator include radiators, coolers, die pads, printed circuit boards, cooling fans, Peltier elements, heat pipes, vapor chambers, metal covers, housings, etc. The heat pipe is, for example, a hollow structure that is cylindrical, approximately cylindrical, or flattened.

[0074] FIG. 2 is a cross-sectional view showing an example of a semiconductor device to which a thermally conductive sheet is applied. For example, as shown in FIG. 2, the thermally conductive sheet 1 is mounted on a semiconductor device 50 built into various electronic devices and sandwiched between a heat generating body and a heat sink. The semiconductor device 50 shown in FIG. 2 includes an electronic component 51, a heat spreader 52, and a thermally conductive sheet 1, and the thermally conductive sheet 1 is sandwiched between the heat spreader 52 and the electronic component 51. The thermally conductive sheet 1 is sandwiched between the heat spreader 52 and the heat sink 53, and together with the heat spreader 52, constitutes a heat dissipation member that dissipates heat from the electronic component 51. The mounting location of the thermally conductive sheet 1 is not limited to between the heat spreader 52 and the electronic component 51, or between the heat spreader 52 and the heat sink 53, and can be appropriately selected according to the configuration of the electronic device or the semiconductor device. The heat spreader 52 is formed, for example, in a rectangular plate shape, and has a main surface 52a facing the electronic component 51 and a side wall 52b standing along the outer periphery of the main surface 52a. The heat spreader 52 has a thermally conductive sheet 1 provided on the main surface 52a surrounded by the side wall 52b, and a heat sink 53 provided, with the thermally conductive sheet 1 interposed between the main surface 52a and the other surface 52c opposite the main surface 52a. EXAMPLES

[0075] Hereinafter, examples of the present technology will be described. Note that the present technology is not limited to these examples.

[0076] <Preparation of Resin Composition> The raw materials used in preparing the resin composition are as follows.

[0077] <Component a> An addition reaction type silicone resin comprising a mixture of an organopolysiloxane having an alkenyl group, a platinum catalyst, and an organopolysiloxane having a hydrosilyl group.

[0078] <Component b> b-1: Spherical magnesium oxide (average particle size 100 μm) b-2: Spherical aluminum oxide (average particle size 20 μm) b-3: Crushed aluminum nitride (average particle size 2 μm) b-4: Crushed aluminum hydroxide (average particle size 5 μm) b-5: Crushed aluminum oxide (average particle size 2 μm)

[0079] <Ingredient c> c-1: Flake graphite (average particle size 2 μm), product name: FT-2 (manufactured by Higashi Nippon Carbon Co., Ltd.) c-2: Flake graphite (average particle size 5 μm), product name: J-CPB (manufactured by Nippon Graphite Trading Co., Ltd.) c-3: Flake graphite (average particle size 10 μm), product name: MF-10N (manufactured by Higashi Nippon Carbon Co., Ltd.) c-4: Melamine cyanurate (average particle size 2 μm), product name: MC-6000 (manufactured by Nissan Chemical Industries, Ltd.) c-5: Melamine cyanurate (average particle size 10 μm), product name: MC-4500 (manufactured by Nissan Chemical Industries, Ltd.) c-6: Flake-shaped boron nitride (average particle size 5 μm), product name: HGP (manufactured by Denka) c-7: Flake-shaped boron nitride (average particle size 22 μm), product name: HS (manufactured by Air Brown)

[0080] <ingredient d> Alkyltrialkoxysilane: n-Decyltrimethoxysilane

[0081] <ingredient e> Phenolic antioxidant, product name: AO-80 (ADEKA)

[0082] Resin compositions consisting of each component shown in Tables 1 to 4 were prepared. Specifically, for component b, component c, component d, and, if necessary, component e, the predetermined amounts shown in the examples and comparative examples in Tables 1 to 4 were added and mixed with a commercially available mixer (Awatori Rentaro, model number: ARV-310, manufactured by Thinky Corporation), and then component a was added and mixed. The rotation speed of the mixer was 1000 rpm. For component b, in Comparative Examples 1 and 4, a mixture of 250 parts by weight of component b-3 (crushed aluminum nitride), 550 parts by weight of component b-2 (spherical aluminum oxide), and 600 parts by weight of component b-1 (spherical magnesium oxide) was used relative to 100 parts by weight of silicone resin. In Comparative Example 2, a mixture of 200 parts by weight of component b-4 (crushed aluminum hydroxide), 400 parts by weight of component b-2 (spherical aluminum oxide), and 400 parts by weight of component b-1 (spherical magnesium oxide) was used relative to 100 parts by weight of silicone resin. In Comparative Example 3, a mixture of 300 parts by weight of component b-5 (crushed aluminum oxide), 600 parts by weight of component b-2 (spherical aluminum oxide), and 600 parts by weight of component b-1 (spherical magnesium oxide) was used relative to 100 parts by weight of silicone resin. In the examples and comparative examples shown in Tables 1 to 4, the weight ratio of the main agent and the curing agent constituting the binder resin was 1:1.

[0083] [Table 1]

[0084] [Table 2]

[0085] [Table 3]

[0086] [Table 4]

[0087] <Preparation of thermal conductive sheet> Using a bar coater, the resin composition was sandwiched between PET films with a release agent and coated to a thickness of 2 mm, and component a was cured to obtain a thermally conductive sheet (thermally conductive sheet before aging). The curing conditions were room temperature for 24 hours.

[0088] <Heat resistance test for thermal conductive sheets> The obtained thermally conductive sheet was subjected to an aging treatment at 170° C. for 500 hours using a constant temperature air blower dryer (manufactured by Tokyo Rikakikai Co., Ltd.), to obtain an aged thermally conductive sheet.

[0089] <Asker C hardness (before aging)> The Asker C hardness of the thermally conductive sheet before aging or after aging was measured according to a method in accordance with JIS K7312. Specifically, five of the above-mentioned 2 mm thick thermally conductive sheets (thermally conductive sheets before aging or after aging) were stacked, and the Asker C hardness was measured 30 seconds after the start of measurement using an Asker C hardness tester (constant pressure loader, CL-150 type (manufactured by Kobunshi Keiki Co., Ltd.)). The results are shown in Tables 5 to 8.

[0090] <Thermal conductivity> Using a thermal resistance measuring device conforming to ASTM-D5470, a load of 1 kgf / cm was applied to the thermal conductive sheet before and after aging. 2 The thermal conductivity (W / (m·K)) of each thermal conductive sheet in the thickness direction was measured by applying a voltage of 100 V to each sheet. The results are shown in Tables 5 to 8.

[0091] <Dielectric breakdown strength> In accordance with a method conforming to JIS C2110-1, an air test electrode jig (product name: TJ-20 (manufactured by Tama Densoku Co., Ltd.) was used to measure the dielectric breakdown voltage (kV / mm) of a thermally conductive sheet molded to a 10 cm square and 1 mm thick in a short-time (rapid voltage increase) test, and the dielectric breakdown strength was calculated using the thickness of the sample at the time of measurement. The results are shown in Tables 5 to 8.

[0092] <Volume resistivity> The volume resistivity (Ω·cm) of the thermal conductive sheet was measured using an ultra-high voltage withstand voltage tester (manufactured by Agilent Technologies) according to the method of JIS K6911. The results are shown in Tables 5 to 8.

[0093] [Table 5]

[0094] [Table 6]

[0095] [Table 7]

[0096] [Table 8]

[0097] From the results of the examples and comparative examples, it was found that the thermal conductive sheet using the resin composition containing components a, b, and c can suppress the decrease in flexibility when placed under high temperatures for a long period of time, compared to the thermal conductive sheet using the resin composition not containing component c. In other words, it was found that the thermal conductive sheet using the resin composition containing components a, b, and c can suppress the increase in hardness (Asker C hardness) before and after aging, compared to the thermal conductive sheet using the resin composition not containing component c. In addition, from the results of the examples and comparative examples, it was found that the thermal conductive sheet using the resin composition containing components a, b, and c does not affect the initial values ​​of physical properties other than Asker C hardness (thermal conductivity, dielectric breakdown strength, volume resistivity) compared to the thermal conductive sheet using the resin composition not containing component c.

[0098] Specifically, the results shown in Tables 1 and 5 show that the thermal conductive sheets of Examples 1 to 7, which used resin compositions containing component a, component b, component c (any one of components c-1 to c-7), and component d, were able to suppress the increase in Asker C hardness after aging relative to the Asker C hardness before aging, compared to the thermal conductive sheet of Comparative Example 1, which used a resin composition not containing component c.

[0099] FIG. 3 is a graph showing the Asker C hardness versus time after aging of the thermally conductive sheets using the resin compositions of Examples 1 to 7 and Comparative Example 1. The horizontal axis in FIG. 3 represents the time of the reliability test (aging treatment at 170°C). The vertical axis in FIG. 3 represents the Asker C hardness of the thermally conductive sheet. As shown in FIG. 3, it was found that the thermally conductive sheets of Examples 1 to 7 can suppress the increase in Asker C hardness 500 hours after the start of aging compared to the Asker C hardness before aging (when the horizontal axis in FIG. 3 is 0 hours) compared to the thermally conductive sheet of Comparative Example 1. Also, as shown in FIG. 3, it was found that the thermally conductive sheets of Examples 1 to 7 can suppress the increase in Asker C hardness 250 hours after the start of aging compared to the Asker C hardness before aging (when the horizontal axis in FIG. 3 is 0 hours) compared to the thermally conductive sheet of Comparative Example 1.

[0100] Furthermore, from the results shown in Tables 1 and 5, it was found that the thermal conductive sheets of Examples 1 to 7, which used a resin composition containing component a, component b, component c (any one of components c-1 to c-7), and component d, were able to reduce the Asker C hardness before aging compared to the thermal conductive sheet of Comparative Example 1, which used a resin composition not containing component c.

[0101] Furthermore, from the results shown in Tables 1 and 5, it was found that the thermal conductive sheets of Examples 1 to 3, which used resin compositions containing flake graphite (components c-1 to c-3) as component c, were able to achieve a lower Asker C hardness before aging compared to the thermal conductive sheets of Examples 4 to 7, which used resin compositions containing flake boron nitride (component c-6, component c-7) or melamine cyanurate (component c-4, component c-5) as component c.

[0102] The results shown in Tables 2 and 6 show that the thermal conductive sheet of Example 8, which used a resin composition containing component a, component b, component c (component c-1), and component d, can suppress the increase in Asker C hardness after aging relative to the Asker C hardness before aging, compared to the thermal conductive sheet of Comparative Example 2, which used a resin composition not containing component c.

[0103] Furthermore, from the results shown in Tables 2 and 6, it was found that the thermal conductive sheet of Example 8, which used a resin composition containing component a, component b, component c (component c-1), and component d, was able to reduce the Asker C hardness before aging compared to the thermal conductive sheet of Comparative Example 2, which used a resin composition not containing component c.

[0104] FIG. 4 is a graph showing the Asker C hardness versus time after aging of the thermally conductive sheets using the resin compositions of Example 8 and Comparative Example 2. The horizontal axis in FIG. 4 represents the time of the reliability test (aging treatment at 170° C.). The vertical axis in FIG. 4 represents the Asker C hardness of the thermally conductive sheet. As shown in FIG. 4, it was found that the thermally conductive sheet of Example 8 can suppress the increase in the Asker C hardness 500 hours after the start of aging compared to the Asker C hardness before aging (when the horizontal axis in FIG. 4 is 0 hours) compared to the thermally conductive sheet of Comparative Example 2. Also, as shown in FIG. 4, it was found that the thermally conductive sheet of Example 8 can suppress the increase in the Asker C hardness 250 hours after the start of aging compared to the Asker C hardness before aging (when the horizontal axis in FIG. 4 is 0 hours) compared to the thermally conductive sheet of Comparative Example 2.

[0105] The results shown in Tables 3 and 7 show that the thermal conductive sheet of Example 9, which used a resin composition containing components a, b, c (component c-1), d, and e, was able to suppress the increase in Asker C hardness after aging relative to the Asker C hardness before aging, compared to the thermal conductive sheet of Comparative Example 3, which used a resin composition not containing component c.

[0106] Furthermore, from the results shown in Tables 3 and 7, it was found that the thermal conductive sheet of Example 9, which used a resin composition containing components a, b, c (component c-1), d, and e, was able to reduce the Asker C hardness before aging compared to the thermal conductive sheet of Comparative Example 3, which used a resin composition not containing component c.

[0107] FIG. 5 is a graph showing the Asker C hardness versus time after aging of the thermally conductive sheets using the resin compositions of Example 9 and Comparative Example 3. The horizontal axis in FIG. 5 represents the time of the reliability test (aging treatment at 170°C). The vertical axis in FIG. 5 represents the Asker C hardness of the thermally conductive sheet. As shown in FIG. 5, it was found that the thermally conductive sheet of Example 9 can suppress the increase in the Asker C hardness 500 hours after the start of aging compared to the Asker C hardness before aging (when the horizontal axis in FIG. 5 is 0 hours) compared to the thermally conductive sheet of Comparative Example 3. Also, as shown in FIG. 5, it was found that the thermally conductive sheet of Example 9 can suppress the increase in the Asker C hardness 250 hours after the start of aging compared to the Asker C hardness before aging (when the horizontal axis in FIG. 5 is 0 hours) compared to the thermally conductive sheet of Comparative Example 3.

[0108] The results shown in Tables 4 and 8 show that the thermal conductive sheets of Examples 10 to 14, which used a resin composition containing component a, component b, component c (component c-1), component d, and component e, with the content of component c being 4.0% by weight or less, were able to suppress the increase in Asker C hardness after aging relative to the Asker C hardness before aging, compared to the thermal conductive sheet of Comparative Example 4, which used a resin composition not containing component c.

[0109] Furthermore, from the results shown in Tables 4 and 8, it was found that the thermal conductive sheets of Examples 10 to 14, which used a resin composition containing component a, component b, component c (component c-1), component d, and component e, with the content of component c being 4.0% by weight or less, also had a lower Asker C hardness before aging than the thermal conductive sheet of Comparative Example 4, which used a resin composition not containing component c.

[0110] FIG. 6 is a graph showing the Asker C hardness versus time after aging of the thermally conductive sheets using the resin compositions of Examples 10 to 14 and Comparative Example 4. The horizontal axis in FIG. 6 represents the time of the reliability test (aging treatment at 170°C). The vertical axis in FIG. 6 represents the Asker C hardness of the thermally conductive sheet. As shown in FIG. 6, it was found that the thermally conductive sheets of Examples 10 to 14 can suppress the increase in Asker C hardness 500 hours after the start of aging compared to the Asker C hardness before aging (when the horizontal axis in FIG. 6 is 0 hours) compared to the thermally conductive sheet of Comparative Example 4. Also, as shown in FIG. 6, it was found that the thermally conductive sheets of Examples 10 to 14 can suppress the increase in Asker C hardness 250 hours after the start of aging compared to the Asker C hardness before aging (when the horizontal axis in FIG. 6 is 0 hours) compared to the thermally conductive sheet of Comparative Example 4.

[0111] Furthermore, the results shown in Tables 1 to 8 show that the thermal conductive sheets of Examples 1 to 14, which used resin compositions containing components a, b, and c, also had good dielectric breakdown strength, volume resistivity, and thermal conductivity before and after aging. [Explanation of symbols]

[0112] 1. Thermally conductive sheet, 2. Binder resin, 3. Thermally conductive filler, 4 Layered materials, 50 Semiconductor device, 51 Electronic components, 52 heat spreader, 52a main surface, 52b side wall, 52c On the other side, 53 Heat sink

Claims

1. A binder resin; A thermally conductive filler; A resin composition comprising a layered material.

2. 2. The resin composition according to claim 1, wherein the content of said layered material is 4.5% by weight or less.

3. 3. The resin composition according to claim 1, wherein the layered material is at least one selected from the group consisting of flake graphite, flake boron nitride, and melamine cyanurate.

4. The resin composition according to claim 3 , wherein the layered material is flake graphite or flake boron nitride.

5. The resin composition according to claim 4, wherein the layered material is flake graphite.

6. 3. The resin composition according to claim 1, wherein the thermally conductive filler is at least one selected from the group consisting of spherical thermally conductive fillers and pulverized thermally conductive fillers.

7. The resin composition according to claim 1 or 2, further comprising an alkoxysilane compound.

8. The resin composition according to claim 1 or 2, further comprising an antioxidant.

9. A thermally conductive sheet which is a cured product of the resin composition according to claim 1 or 2.

10. The thermal conductive sheet according to claim 9, having a thermal conductivity of 3 W / (m·K) or more.

Citation Information

Patent Citations

  • Gel with improved thermal stability

    JP2014534292A

  • Thermal conductive silicone composition and thermal conductive silicone molded product

    JP2016030774A